Assessment of polyphenolic profile and antibacterial activity of pomegranate peel (Punica granatum) flour obtained from co-product of juice extraction - Gullon, Beatriz; Pintado, Manuela E.; Pérez-Álvarez, José A.; Viuda-Martos, Manuel (Food control, 2016)
The aim of this work were to determine the polyphenolic profile and the antibacterial properties of pomegranate peel flour (PPF), in view to its application in the food industry as potential antimicrobial “natural” agent. For thus, the antibacterial properties of PPF were tested against: Listeria monocytogenes, Listeria innocua, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Salmonella sp. bacterial strains. The polyphenolic profile was determined by HPLC. The Total Phenolic and Total Flavonoid content were also determined. The HPLC analysis of the PPF, showed a total of eight phenolic compounds. Punicagalin was the main component found in PPF (16.67 mg/g) followed by ellagic acid (0.15 mg/g). PPF had antibacterial activity against all bacteria tested with minimal inhibitory concentrations comprised between 20 and 50 mg/mL. The antimicrobial activity was in a decreasing order: Salmonella sp = E. coli = S. aureus = L. monocytogenes > P. aeruginosa > L. innocua. The antibacterial properties of pomegranate peel flour suggested that it is a promising antibacterial agent.